Medinilla malabrigoi (Melastomataceae), a new species from forests over limestone in Samar Island, Philippines - Adorador, Jiro T.; Meneses-Adorador, Zhereeleen D.; Quakenbush, J. Peter (Phytotaxa, 2021)
A new species of Medinilla, M. malabrigoi, from forests over limestone in Samar Island, Philippines is described and illustrated. It differs from the species of the M. polillensis alliance, herein defined, which includes M. polillensis s.l. and M. peltata, in its erect shrubby habit; sessile, narrowly lanceolate, 3-plinerved leaf with cordate to subcordate base; umbellate inflorescence; and flared, reflexed calyx at anthesis. Morphological and distributional comparisons with the most similar congeners are provided, as well as information on habitat and conservation status. Likewise, a taxonomic key to the Medinilla of Samar Island is herein devised.